Noise reduction of mine and tunnel ventilation; investigations on scale models and methods to determine noise reduction - Arand, Sally (My University, 2023)
Ventilation systems used in mines and tunnels contain big axial flow fans, which dominate the sound environment together with the noise generated from heavy machinery. To fulfil the demands regarding work-placement and environmental regulations and with increasing awareness of noise induced health issues, the reduction of the emitted sound is investigated in a thesis project with practical measurements and simulations. To do fast investigations a scale model of the ventilation system was designed. The fan scaling laws, which are used to scale fan properties between different fan sizes, showed, that by reducing the fan size and the rotational speed the fan performance will decrease highly. The resulting effect on the flow properties is rather small. The blade passage frequency will change, which leads to a change in the acoustic similarity. CFD simulations were performed in Comsol Multiphysics 6.1 to investigate the pressure and velocity field closely over a perforated plate and around a centrumbaffle, which are both part of the silencer of the ventilation system. The results showed a laminar-sublayer close to the wall and an increase in the fluctuations of the velocity and the pressure in the flow duct when adding the centrum-baffle. In the practical part of the thesis the silencer of the ventilation system was scaled and its acoustic properties were determined with measurements. The transmission loss measurement methods were compared by using the two room method with microphones and a sound intensity probe. Both methods showed similar results. Insertion loss and level difference were measured in another setup. Overall there was no big difference between the silencer characteristics measured from the different methods. It was found that the most effective reduction is brought from the absorption material. The perforated plate does not add to the noise reduction. At last an acoustic simulation for the silencer was set up in Comsol to investigate the transmission loss of the silencer further. Due to limitations in computational resources, the model is restricted to plane wave excitation, which limits the accuracy of the model and the possibility to directly compare the measurements with the simulation results. But both show the most effect due to the absorber and no added reduction by the perforated plate.
Keywords: Mining, ventilation, transmission loss, silencer, pressure measurement, intensity measurement, CFD, FEM, scaling